Alu‐mediated Xq24 deletion encompassing CUL4B, LAMP2, ATP1B4, TMEM255A, and ZBTB33 genes causes Danon disease in a female patient. Issue 1 (15th November 2019) - Majer, Filip; Kousal, Bohdan; Dusek, Petr; Piherova, Lenka; Reboun, Martin; Mihalova, Romana; Gurka, Jiri; Krebsova, Alice; Vlaskova, Hana; Dvorakova, Lenka; Krihova, Jana; Liskova, Petra; et al.
Abstract: Cullin 4B ( CUL4B ), lysosomal‐associated membrane protein Type 2 ( LAMP2 ), ATP1B4, TMEM255A, and ZBTB33 are neighboring genes on Xq24 . Mutations in CUL4B result in Cabezas syndrome (CS). Male CS patients present with dysmorphic, neuropsychiatric, genitourinary, and endocrine abnormalities. Heterozygous CS females are clinically asymptomatic. LAMP2 mutations cause Danon disease (DD). Cardiomyopathy is a dominant feature of DD present in both males and heterozygous females. No monogenic phenotypes have been associated with mutations in ATP1B4, TMEM255A, and ZBTB33 genes. To facilitate diagnostics and counseling in CS and DD families, we present a female DD patient with a de novo Alu ‐mediated Xq24 rearrangement causing a deletion encompassing CUL4B, LAMP2, and also the other three neighboring genes. Typical to females heterozygous for CUL4B mutations, the patient was CS asymptomatic, however, presented with extremely skewed X‐chromosome inactivation (XCI) ratios in peripheral white blood cells. As a result of the likely selection against CUL4B deficient clones, only minimal populations ( 3%) of LAMP2 deficient leukocytes were identified by flow cytometry. On the contrary, myocardial LAMP2 protein expression suggested random XCI. We demonstrate that contiguous CUL4B and LAMP2 loss‐of‐function copy number variations occur and speculate that male patients carrying similar defects could present with features of both CS and DD.